Pertussis Infections Among Pregnant Women in the United States, 2012–2017. (7th August 2020) - Skoff, Tami H; Faulkner, Amanda E; Liang, Jennifer L; Barnes, Meghan; Kudish, Kathy; Thomas, Ebony; Kenyon, Cynthia; Hoffman, Marisa; Pradhan, Eva; Liko, Juventila; Hariri, Susan
Abstract: Background: Little is known about pertussis among pregnant women, a population at increased risk for severe morbidity from respiratory infections such as influenza. We used the Centers for Disease Control and Prevention's Enhanced Pertussis Surveillance (EPS) system to describe pertussis epidemiology among pregnant and nonpregnant women of childbearing age. Methods: Pertussis cases in women aged 18–44 years with cough onset between 1 January 2012 and 31 December 2017 were identified in 7 EPS states. Surveillance data were collected through patient and provider interviews and immunization registries. Bridged-race, intercensal population data and live birth estimates were used as denominators. Results: We identified 1582 pertussis cases among women aged 18–44 years; 5.1% (76/1499) of patients with a known pregnancy status were pregnant at cough onset. Of the pregnant patients with complete information, 81.7% (49/60) reported onset during the second or third trimester. The median ages of pregnant and nonpregnant patients were 29.0 and 33.0 years, respectively. Most pregnant and nonpregnant patients were White (78.3% vs. 86.4%, respectively; P = .09) and non-Hispanic (72.6% vs. 77.3%, respectively; P = .35). The average annual incidence of pertussis was 7.7/100000 among pregnancy women and 7/3/100000 among nonpregnant women. Compared to nonpregnant patients, more pregnant patients reported whoop (41.9% vs. 31.3%, respectively), posttussive vomiting (58.1% vs. 47.9%, respectively), and apnea (37.3% vs. 29.0%, respectively); however, these differences were not statistically significant ( P values > .05 for all). A similar proportion of pregnant and nonpregnant patients reported ever having received Tdap (tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis vaccine; 31.6% vs. 32.7%, respectively; P = .84). Conclusions: Our analysis suggests that incidence of pertussis and clinical characteristics of disease are similar among pregnant and nonpregnant women. Continued monitoring is important to further define pertussis epidemiology in pregnant women. Abstract : During 2012–2017, 1582 pertussis cases occurred among women aged 18–44 years; 5.1% (76/1499) of patients with known status were pregnant at cough onset. Pertussis incidences and the clinical presentations of infection were similar between pregnant and nonpregnant women.